A Classic Clinical Case: Neutrophilic Eccrine Hidradenitis - Ana-Maria Copaescu; Jean-François Castilloux; Myrna Chababi-Atallah; Christian Sinave; Janie Bertrand (Karger Publishers, 2013)
Background: Neutrophilic eccrine hidradenitis (NEH) is a rare condition described mostly in adult patients receiving chemotherapy for acute myelogenous leukemia. When it affects the facial region, it can mimic cellulitis and delay the diagnostic, thus proper recognition is essential. Objective: This article describes a classic case of NEH. We will review the diagnostic, the differential diagnostic (mostly cellulitis) and the management of this condition. Methods: After a literature review, the patient's file was properly studied in order to portray a clear picture of this condition. Medical photographs and appropriate physical examination upon presentation are also included. Results: The diagnostic for NEH was suggested by the clinical presentation and confirmed histopathologically (skin biopsy). Conclusion: The diagnostic of NEH is essential in order to prevent multiple unnecessary antibiotics.